Organic THz Crystals Based on Off-Diagonal Optical Nonlinearity with Optimal In-Plane Polar Axis - Lee, Chae Won; Kim, Chaeyoon; Yoon, Woojin; Yun, Hoseop; Jazbinsek, Mojca; Rotermund, Fabian; Kwon, O. Pil (Advanced Optical Materials, 2024)
Highly efficient off-diagonal THz generators based on novel organic nonlinear optical single crystals with optimal polar axis orientation in the as-grown crystal morphology are introduced. The newly developed fluorinated and non-fluorinated cationic chromophores exhibit a non-centrosymmetric crystal structure with P21 space group symmetry in the crystalline phase. In particular, PB5FB-T (5-fluoro-2-(4-(2-(hydroxymethyl)pyrrolidin-1-yl)styryl)-3-methylbenzothiazol-3-ium 4-methylbenzenesulfonate) crystals have an in-plane polar axis, along with a top-level off-diagonal component of the nonresonant effective first hyperpolarizability of ≈100 × 10−30 esu. This stands in stark contrast to previously reported organic THz crystals, which either show a small off-diagonal optical nonlinearity with an in-plane polar axis or a large off-diagonal optical nonlinearity with an almost out-of-plane polar axis. Employing an off-diagonal THz generation configuration, PB5FB-T crystals generate a THz electric field approximately four times higher than previously reported benchmark analogous crystals with a polar axis nearly out-of-plane. Moreover, PB5FB-T crystals yield smooth THz spectral shapes without significant absorption dimples up to 6 THz when utilizing 130-fs pump pulses at the wavelength of 1300 nm.
Keywords: As-grown crystal; Axis orientation; Crystal morphologies; Non-linear optical; Optical nonlinearity; Organic crystal; Organics; Out-of-plane; Polar axis; Tera Hertz; nonlinear optics; organic crystals; terahertz waves